2021
DOI: 10.1530/ec-21-0500
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adrenal insufficiency among patients with euvolemic hyponatremia

Abstract: Background: The diagnosis of SIAD requires the exclusion of secondary adrenal insufficiency (AI) among patients with euvolemic hyponatremia (EuVHNa). Studies have suggested about 2.7% to 3.8% of unselected patients presenting to the emergency room with EuVHNa have undiagnosed AI and it is as high as 15% among patients admitted to specialized units for evaluation of hyponatremia. Objective: To study the prevalence of AI among inpatients with EuVHNa in a general medical ward setting Methods: This was a prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Conditions including bronchial carcinoma, acute respiratory failure, psychosis, meningitis, hydrocephaly, encephalitis, and spinal cord lesions may also be characterized by euvolemic hyponatremia secondary to SIADH [ 18 - 20 ]. Hyponatremia resulting from SIADH can also be a frequent complication during pulmonary infections (pneumonia) and central nervous system (CNS) infections, whereby the critical mechanisms involved in SIADH development are attributed to hypoxia and intravascular volume depletion [ 21 , 22 ]. Given that SIADH is more frequently observed in patients with greater disease severity as well as inflammation, it is plausible that nonosmotic stimulation of ADH secretion may result from nonosmotic stimulation of ADH secretion triggered by excessive amounts of pro-inflammatory cytokines released, especially interleukin 6 (IL-6) [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…Conditions including bronchial carcinoma, acute respiratory failure, psychosis, meningitis, hydrocephaly, encephalitis, and spinal cord lesions may also be characterized by euvolemic hyponatremia secondary to SIADH [ 18 - 20 ]. Hyponatremia resulting from SIADH can also be a frequent complication during pulmonary infections (pneumonia) and central nervous system (CNS) infections, whereby the critical mechanisms involved in SIADH development are attributed to hypoxia and intravascular volume depletion [ 21 , 22 ]. Given that SIADH is more frequently observed in patients with greater disease severity as well as inflammation, it is plausible that nonosmotic stimulation of ADH secretion may result from nonosmotic stimulation of ADH secretion triggered by excessive amounts of pro-inflammatory cytokines released, especially interleukin 6 (IL-6) [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…A recent paper from North India suggested that 3.5% (5/141) of patients presenting to the medical ward with euvolemic hyponatremia had adrenal insufficiency secondary to undocumented steroid use including contamination of indigenous medications with steroids. [ 1 ]…”
mentioning
confidence: 99%